The repressor PrtR1 and the global H-NS-like regulators MvaT and MvaV enable the fine-tuning of R-tailocin expression in Pseudomonas protegens - Clara Margot Heiman; Hammam Antar; Florian Fournes; Christoph Keel; Jordan Vacheron (BMC Microbiology)
Abstract Background Bacteria rely on an arsenal of weapons to challenge their opponents in highly competitive environments. To specifically counter closely related bacteria, specialized weapons with a narrow activity spectrum are deployed, particularly contractile phage tail-like particles or R-tailocins. Their production leads to the lysis of the producing cells, indicating that their expression must be carefully orchestrated so that only a small percentage of cells produce R-tailocins for the benefit of the entire population. Results In this study, we set out to better understand how the production of these phage tail-like weapons is regulated in environmental pseudomonads using the competitive plant root colonizer and environmental model strain Pseudomonas protegens CHA0. Using an RNA sequencing (RNA-seq) approach, we found that genes involved in DNA repair, particularly the SOS response program, are upregulated following exposure of the pseudomonad to the DNA-damaging agents mitomycin C and hydrogen peroxide, while genes involved in cell division and primary metabolism are downregulated. The R-tailocin and prophage gene clusters were also upregulated in response to these DNA damaging agents. By combining reverse genetics, transcriptional reporters and chromatin immunoprecipitation sequencing (ChIP-seq), we show that the R-tailocin locus-specific LexA-like regulator PrtR1 represses R-tailocin gene expression by binding directly to the promoter region of the cluster, while the histone-like nucleoid structuring (H-NS) proteins MvaT and MvaV act as master regulators that indirectly regulate R-tailocin cluster expression. Conclusion Our results suggest that at least these three regulators operate in concert to ensure tight control of R-tailocin expression and cell lytic release in environmental Pseudomonas protegens strains.